Post-partum intrauterine contraceptive device: acceptability and safety - Tomar, Bhawna; Saini, Vandana; Gupta, Mamta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Antenatal period is the ideal time for counselling regarding contraception. PPIUCD is a long term reversible method for unmet need of contraception in women of reproductive age. The objectives of this study were to determine proportion of women accepting PPIUCD insertion, their socio-demographic, obstetrics characteristics, reason for acceptance, denial, rates of expulsion, complications and continuation rate till 10 weeks after insertion. Methods: A prospective descriptive study on 300 consented women was done in 2012-2013. A structured questionnaire and performa were used to obtain data. PPIUCD (CuT380A) was inserted in these women and were followed up till 10 weeks post insertion. Results: Out of 300 women counselled, only 85 accepted PPIUCD giving an acceptance rate of 28.33%. Women who had short inter-conceptional period or those who had previously used interval IUCD were significantly associated with greater acceptance. Fear of pain, heavy bleeding and infertility when planning next pregnancy were the most common reasons for denial. Continuation rate was 86.89% at 10th week after insertion. No major complication was observed i.e. perforation, infection and pregnancy. Conclusions: PPIUCD is quite safe method of contraception. Adequate counselling and clarification of myths associated with PPIUCD use can help acceptance and meet the unmet needs of contraception in post-partum period and even later in reproductive age women.